"Ain't It a Ripping Night": Alcoholism and the Legacies of Empire in Salman Rushdie's Midnight's Children. Issue 3 (3rd April 2018) - Goodman, Sam
ABSTRACT: In the era of decolonisation that followed the Second World War, various authors sought to engage with India and the Empire's past anew throughout their novels, identifying medicine and illness as key parts of Imperial authority and colonial experience. Salman Rushdie's approach to the Raj in Midnight's Children (1981) focused on the broad sweep of colonial life, juxtaposing the political and the personal. This article argues that Rushdie explores the history of colonial India by employing alcohol and alcoholism as lenses through which to explore the cultural, political and medical legacies of Empire. Through analysis of Midnight's Children as well as a range of medical sources related to alcohol and inebriation, it will illustrate how drinking is central to Rushdie's approach to secular and religious identities in newly independent India, as well as a means of satirising and undermining the supposed benefit that Empire presented to India and Indians.